REALITAS KEKERASAN DAN PELECEHAN PEREMPUAN DI TEMPAT KERJA: ANALISIS PERSPEKTIF GENDER - Putri, Della First Tania; Wilodati, Wilodati; Wulandari, Puspita (Kafa`ah: Journal of Gender Studies, 2024)
The amount of violence and harassment that women still experience in the workplace shows that there is no safe and comfortable place for women in the public environment, especially the workplace. The 2023 International Labour Organisation (ILO) Survey results also indicate that Indonesia is among the nations experiencing an emergency scenario of workplace violence. Based on this background, the research aims to shed light on the reality of workplace violence and harassment against women from a gender perspective. The literature review method was employed in this study. This approach uses numerous references from books, articles, and earlier research journals. This study used secondary data for its data collection. International journal databases like Google Scholar, Pubmed, Researchget, and Crossref were used for journal searches. The terms "violence and harassment of women in the workplace" and "violence against women at the workplace" are used in the search for data sources. The findings of the research point to the complexity of the issue of violence and harassment against women in the workplace, which is influenced by a variety of individual factors, structures, and norms. Through the individual aspect, it is understood that women are always portrayed by inherent gender stereotypes that can lead to violence and harassment. Meanwhile, through the aspects of structure and norms, it is understood that there is a role of power relations and hierarchical structures attached to gender identity in shaping an environment that allows violence and harassment to occur. A strategic step that can be taken is to incorporate the institutionalisation of gender issues coupled with an understanding of gender from the human side to place every gender, both women and men, together to feel safe.